KEPEMIMPINAN HORIZONTAL SEBAGAI SENI KEPEMIMPINAN UNTUK SEMUA ORANG DALAM PENERAPANYA DI ORGANISASI - Ranti Nuranita (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
The leadership role is very important as a determinant of achieving goals both in state and in organization. To produce quality leaders, a leadership concept is needed that can be applied to all the resources involved, both for leaders and employees, it’s called horizontal leadership, this study aims to find out how horizontal leadership art, aspects that must be possessed in horizontal leadership art and how its application in the organization. The method used is literature review, both books and previous research results. The theory used is the theory of horizontal leadership from Christopher P Neck and leadership 3.0 from Ardhi Ridwansyah. The results of this study are that leadership is not only born, inherited, or based on title and position, but also leadership can we grow from within a person naturally and naturally. With the potential already possessed, a person can move and influence themselves and others voluntarily without coercion, without a position (horizontal leadership). The aspects of horizontal leadership are: (physical aspects), (intellectual aspects), (emotional aspects), (aspects of social ability), (personal aspects), (moral aspects). The results of previous studies show that with the implementation of horizontal leadership, employee motivation and job satisfaction increase. Key Words: leadership 3.0; horizontal leadership; self leadership